Ancestralidade biogeográfica de quatro grupos populacionais do Rio Grande do Sul (RS), Brasil, por sequenciamento massivo paralelo de 165 marcadores genéticos - Felkl, Aline Brugnera (2020)
Forensic DNA phenotyping (FDP) includes biogeographic ancestry (BGA) inference and externally visible characteristics (EVCs) prediction directly from an evidential DNA sample as alternatives to provide valuable intelligence when conventional DNA profiling fails to achieve identification. In this context, the application of Massively Parallel Sequencing (MPS) methodologies, which enables simultaneous typing of multiple samples and hundreds of forensic markers, has been gradually implemented in forensic genetic casework. The Precision ID Ancestry Panel (Thermo Fisher Scientific, Waltham, USA) is a forensic multiplex assay consisting of 165 autosomal SNPs designed to provide biogeographic ancestry information. In this work, a sample of 250 individuals from Rio Grande do Sul (RS) State, southern Brazil, apportioned into four main population groups (African-, European-, Amerindian-, and Admixed-derived Gauchos), was evaluated with this panel, to assess the feasibility of this approach in a highly heterogeneous population. Forensic descriptive parameters estimated for each population group revealed that this panel has enough polymorphic and informative SNPs to be used as a supplementary instrument in forensic individual identification and kinship testing regardless of ethnicity. No statistically significant deviation from Hardy-Weinberg equilibrium was observed after Bonferroni correction. However, seven loci pairs displayed linkage disequilibrium in pairwise LD testing (p < 3.70 × 10-6). Interpopulation comparisons by FST analysis, MDS plot, and STRUCTURE analysis among the four RS population groups apart and along with 89 reference worldwide populations demonstrated that Admixed- and African-derived Gauchos present the highest levels of admixture and population stratification, whereas European- and Amerindian-derived exhibit a more homogeneous genetic conformation.